Managerial Solution for Hospital-Acquired Infections - Parsia, Yasaman; Puteri Fadzline, Muhamad Tamyez; Sorooshian, Shahryar (IEOM Society International, 2017)
Hospital-acquired infections are not only a major concern for hospitals, but also global health society. Life and cost burden of the hospital-acquired infection is very much noticeable. It is widely stated that hospital-acquired infection is not a local issue; it is a challenging global health-related issue. It results a noticeable mortality rate. Although many prevention policies and booklets were distributed by different hospital managers for staffs, visitors and patients use, the productivity of the hard-copy booklet method were not encouraging enough. Hospital-acquired infection is still a serious problem faced by the ministry of health and hospital policy makers. The main objective of this study is to provide an applicable proposal to encourage mobile application software, active in hospital sites, in order to guide hospital staffs, visitors, and patients on Hospital-acquired infections control methods. This study is with the use of qualitative approached in research. A literature review with additional site observations has been conducted by the researchers to achieve the main objective of this research. As the result of this study, we find that mobile health could be an effective method to solve the hospital-acquired infection issue. Hospital managers with the support of the ministry of health could provide a free of charge mobile application software in the area of related hospital units for the visitors, staffs, and patients. The software could be planned to show prevention techniques based on each site unit. The users will easily install the application on their smartphone, for free and start reading the prevention methods to enhance their knowledge.